2021
DOI: 10.3389/fpsyg.2021.650070
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Personality Traits on School Bullying: A Moderated Mediation Model

Abstract: We recruited 1,631 middle and high school students to explore the relationship between personality traits and school bullying, and the moderated and mediating roles of self-concept and loneliness on this relationship. Results showed that (1) neuroticism had a significant positive predictive effect on being bullied, extroversion had a significant negative predictive effect on being bullied, and agreeableness had a significant negative predictive effect on bullying/being bullied; (2) loneliness played a mediatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Studies have noted that being bullied persists in children over time [ 28 ], which indicates that it is influenced by stable personality traits. Some studies have found a significant positive correlation between neuroticism and victimization [ 29 ]. The characteristics of high neuroticism make it difficult to form positive relationships with others, and therefore, individuals cannot receive strong social support from peers, resulting in a lower status in the peer group.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have noted that being bullied persists in children over time [ 28 ], which indicates that it is influenced by stable personality traits. Some studies have found a significant positive correlation between neuroticism and victimization [ 29 ]. The characteristics of high neuroticism make it difficult to form positive relationships with others, and therefore, individuals cannot receive strong social support from peers, resulting in a lower status in the peer group.…”
Section: Introductionmentioning
confidence: 99%
“…The callous-unemotional trait is a personality trait that treats others with indifference, lacks culpability and empathy, and is characterized by stability, severity, and ease of aggression ( Xiao et al, 2014 ). Most of the studies that have been conducted have used callous-unemotional traits as a predictor, such as being able to predict bullying behavior positively ( Zhang et al, 2023 ) and cyberbullying perpetration ( Fang and Wang, 2020 ). However, as a personality trait-like variable, the callous-unemotional traits are usually moderate.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars around the world have begun to explore the causes of school violence from the perspectives of culturally transformative education [11], adolescent personality traits [12,13], student physicality [14], family background [15], teaching climate [16], and social capital [17] in order to prevent or reduce the occurrence of school violence, and have proposed violence prevention measures such as dialogue models [18], drama therapy programs [19], and community participation integrated models [20,21]. Benefiting from these important research findings, the majority of schools around the world now have implemented prevention and control efforts that are based on safety education for school violence, with proactive interventions such as increased surveillance equipment and patrols [22].…”
Section: Introductionmentioning
confidence: 99%